Parameter analysis and modification of transmission loss models for multi-layered cavity walls. Issue 4 (December 2021) - Tsay, Yaw-Shyan; Lin, Chuan-Hsuan
Multi-layer cavity wall (MCW) systems, which refer to each panel in the structure being made up of two or more layers of lightweight board, have become more widely used. However, unlike the detailed approaches that were available for predicting single-layer cavity walls (SCW), few studies have addressed the MCW involving different layers attached together. In this research, we applied two theoretical models of SCW, analyzed the key parameters and modify to have appropriate application for MCW. The predictive capability of the models was then evaluated by comparing them with results of experiment and commercial software. The results showed that Sharp's model was suggested only when the thickness of the steel stud of about 0.75 mm. Through modifying the input values of the compliance of steel ( CM ), attenuation factor ( F ) and the limiting angle of incident (θ L ) in Davy's model, and the prediction of the proposed model showed great consistent with experiments.